2023
DOI: 10.18063/ijb.752
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of biocompatible BSA-GMA and two-photon polymerization of 3D hydrogels with free radical type I photoinitiator

et al.

Abstract: Although the development of three-dimensional (3D) printing technology is growing rapidly in the biomedical field, it remains a challenge to achieve arbitrary 3D structures with high resolution and high efficiency. Protein hydrogels fabricated by two-photon polymerization (TPP) have excellent mechanical properties, high precision, and 3D architecture. However, a large number of the amino acid group in bovine serum albumin (BSA) would be consumed when the protein-based hydrogels use dyes of free radical type II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…In the case of light activation (808 nm, 5 min), an increase to 32% was released, due to hydrogel swelling and drug release, remaining rather low. Based on previously published literature, BSA molecules are carrying, like p-EVs, negative charges at physiological pH 7.4 [ 56 ]. It was speculated that BSA with a low pI might effectively bind to a Gel-based hydrogel matrix by electrostatic attraction [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the case of light activation (808 nm, 5 min), an increase to 32% was released, due to hydrogel swelling and drug release, remaining rather low. Based on previously published literature, BSA molecules are carrying, like p-EVs, negative charges at physiological pH 7.4 [ 56 ]. It was speculated that BSA with a low pI might effectively bind to a Gel-based hydrogel matrix by electrostatic attraction [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of this advantage, Teng Li et al used glycidyl methacrylate (GMA) to modify BSA molecules for various BSA-GMA materials, for the purpose of two-photon polymerization with one type of water-soluble free radical type I photoinitiator. 50 This so-called BSA-GMA hydrogel structure showed high level of autofluorescence imaging, pH responsiveness, and biocompatibility, which show potential in the biomedical field like tissue engineering to cater to many specific needs. The ability to tailor and strategically design biomaterials of TPP can make a difference in the biomedical field, even in cell culture.…”
Section: Vatphotopolymerization-based Bioprintingmentioning
confidence: 99%
“…The resulting soft material showed that chondrocytes could attach and proliferate within a 3D stable structure with pH responsiveness. 128 Concurrently with the incorporation of proteins in the scaffold design, Sk and colleagues (2021) evaluated the introduction of gelatin in a GMA scaffold photo-crosslinked employing Irgacure-2959 (a PI), which promoted the increase in the size of the pores and enhanced the cell differentiation, viability, and proliferation, postulating the material as a potential scaffold for liver. 129 While this work does not comprehensively describe all the published literature on PSs used in the biomaterials field, additional relevant examples are presented in Table S1 (ESI †).…”
Section: Photosensitive Molecules In Biomaterials Developmentmentioning
confidence: 99%